Organic Ligand‐Free ZnO Quantum Dots for Efficient and Stable Perovskite Solar Cells (Adv. Funct. Mater. 49/2022). (2nd December 2022) - Chavan, Rohit D.; Wolska‐Pietkiewicz, Małgorzata; Prochowicz, Daniel; Jędrzejewska, Maria; Tavakoli, Mohammad Mahdi; Yadav, Pankaj; Hong, Chang Kook; Lewiński, Janusz
Abstract : Less is More In article number 2205909, Janusz Lewiński, Chang Kook Hong, and co‐workers demonstrate a novel approach to low‐temperature processable and inherently pure ZnO electron transport layer (ETL) for highly stable planar heterojunction perovskite solar cells (PSCs) based on organic ligand‐free ZnO quantum dots. The champion PSC achieved a power conversion efficiency of 20.05%, the state‐of‐the‐art performance among reported non‐passivated pure‐ZnO ETL‐based PSCs.